The role of sex hormones, waist circumference, BMI and Leptinemia in patients with acute renal failure. - El-Yassin, Hedef Dhafir; Hani, Hind; Jalal, Maysaa (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Acute renal failure is characterized by impaired excretory endocrine homeostatic and metabolic functions of the kidneys. Objective: The aim of this study is to look for the role of sex hormones, waist circumference and leptinemia in patients with acute renal failure. Subjects and Methods: 55 subjects were involved in this study, 30 had acute renal failure and the remaining 25 subjects were normal healthy individuals who served as a control. The age range of the patients was between 25 and 45 years with a mean of 37±8.2 years. Five mls of blood were withdrawn from each subject by vein puncture. Enzyme linked immuno assay (ELISA) was used for the measurement of serum leptin level. Radio immuno assay (RIA) technique was used for the measurements of testosterone and estradiol levels. Data were expressed as mean±SD. Results were evaluated using the student t-test for paired data. Conventional methods were used for the correlation and regression analyses. Results: Patients with acute renal failure show a significant increase in leptin level, BMI and waist circumference than healthy group. On the other hand, testosterone level shows significant decrease while estradiol serum level shows a significant increase when compared with the healthy group in both genders although more significant in females. Females with acute renal failure have significantly higher level of leptin than in males with acute renal failure as well as the anthropometrical measurements (BMI & waist circumference). Conclusion: Increased level of serum leptin and estradiol in acute renal failure is a reflection of increased waist circumference of the patients and the effected renal parenchyma which make the ability of the kidney for biodegradation very poor. On the other hand testesteron has a significant effect on serum leptin levels as can be seen through its positive effect in males rather in females.